Leveraging Oil and Gas Industry for the Development of a Competitive Private Sector in Uganda - World Bank (Washington, DC, 2015)
The study represents a background study for the proposed Uganda Country Economic Memorandum (CEM), which seeks to address the issue of efficient use of oil resources and examine synergies between the oil industry and the rest of the economy, through growth poles or linkages. The oil industry can help Uganda to promote robust growth in the economy. However, it is important to keep in mind that it will take a number of years until oil revenues start flowing into Uganda s economy. After the Final Investment Decision (FID) is reached, it will take time to develop the oil fields and start oil production. In the meantime, there are immediate opportunities opening up for Uganda s businesses to supply the oil industry with goods and services. In most cases, Uganda s suppliers, especially micro, small and medium enterpises (MSMEs), are not expected to become first tier contractors to the International Oil Company (IOCs). The main objective of this study is to provide recommendations to the Government of Uganda (GoU) on policies and strategies of leveraging the oil discoveries for the development of the national economy in order to transform the oil resources into sustained growth. The study reviews the typology of policies for local sourcing used in the world. It includes ample examples of other countries experiences with developing their local content policies and providing support to priority sectors to boost local content which could be useful for Uganda from the standpoint of lessons learned. The study conducts a detailed analysis of the binding constraints faced by domestic oil and gas suppliers in Uganda, takes stock of existing national content support initiatives and identifies areas which are in urgent need of further support. The study examines how the oil sector can be used as a driver of agriculture and fisheries sectors in the Albertine Region and other regions of Uganda from the standpoint of food supply to the oil camps.